Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan PT. Lion Metal Works Tbk. Periode 2016-2021 - Nur Amalia; Nurwani; Yenni Samri Juliati Nasution (Journal Research of Economic and Bussiness, 2023)
The purpose of this study is to determine the financial performance of PT. Lion Metal Works Tbk. 2016-2021 if measured through liquidity, solvency, profitability and activity ratios. This research is a quantitative. The type of data used is quantitative data. The results of the study revealed 2 ratios of good scores and 2 ratios of bad scores. The liquidity ratio in the industry standard, current ratio is 2.0 in 2016-2019 the value is 3,56; 3,27; 3,5; 3,82. In 2020 there will be a significant increase of 6,7 then in 2021 the value is 3,25. The company's solvency ratio shows good condition, the industry standard debt to asset ratio is 35%, 2016-2017 injuries are 31%, 34%, 2018-2020 32%, last 2021 is 36%. The profitability ratio shows that the company is not doing well, the indicator is the net profit margin, the industry standard is 20% for 2016-2021, a loss of 11%, 3%, 3%, 0%, -3%, -1%. Likewise, the activity ratio shows that the condition is not good, one of the indicators is the fixed assets turn over ratio, the industry standard, which is 5 times seen in 2016-2021 payments of 2,77; 2,7; 2,36; 2,04; 1,63; 1,50